PENGEMBANGAN APLIKASI BELAJAR PEMBELAJARAN IPA DI SD BERBASIS HOTS DIMENSI METAKOGNITIF DENGAN PENDEKATAN TPACK - Muhamad Rosidin; A. Syachruroji; Nana Hendracipta (Jurnal Pendidikan Dasar, 2023)
Abstract: Education in Indonesia has been disrupted by the COVID-19 virus pandemic which has caused learning to be carried out at home, and the government is trying to do its best in school policies, which eventually some schools have carried out online learning and offline learning with the imposition of restrictions. The policy eventually created new problems mainly due to the unpreparedness of schools to face online learning. The unpreparedness is caused by several factors, one of which is the ability of teachers to integrate technological and information advances into learning. The development of technology requires humans to have a high level of thinking ability, while the ability to think needs to be trained in the younger generation at the elementary school level. This study uses the RD (Resarch and development) method which aims to find out how the process of making learning applications, the feasibility of learning applications, student and teacher responses to metacognitive dimensions of HOTS-based learning applications with the TPACK approach. The metacognitive dimension HOTS-based learning application with the TPACK approach is an interactive learning media in the form of an android application that contains learning menus such as learning videos, LKPD, E-Books, online multiplayer quizzes, and learning implementation plans to provide an overview of the process of learning activities using learning applications. The learning application received a positive response from students and teachers with a percentage score of 91.04% of the 25 student respondents which means it belongs to the "excellent" category, and 90.80% of the 7 teacher respondents which means it is included in the "excellent" category which indicates the success of this research.Keywords: HOTS-based learning apps, TPACK approach, metacognitive dimensions, elementary school.Â Â Abstrak: Pendidikan di Indonesia dewasa ini telah terganggu oleh adanya pandemi virus covid-19 yang menyebabkan pembelajaran dilakukan dirumah, dan pemerintah berupaya melakukan yang terbaik pada kebijakan-kebijakan sekolah yang akhirnya beberapa sekolah ada yang melakukan pembelajaran dalam jaringan (daring) dan pembelajaran luar jaringan (luring) dengan pemberlakuan pembatasan. Kebijakan tersebut akhirnya menimbulkan masalah baru terutama karena ketidaksiapan sekolah menghadapi pembelajaran dalam jaringan (daring). Ketidaksiapan tersebut disebabkan oleh beberapa faktor salah satunya adalah kemampuan guru dalam mengintegrasikan kemajuan teknologi dan informasi ke dalam pembelajaran. Dengan semakin pesatnya perkembangan teknologi mengharuskan manusia memiliki kemampuan berpikir tingkat tinggi, adapun kemampuan berpikir tersebut perlu dilatih pada generasi muda di tingkat sekolah dasar. Penelitian ini menggunakan metode RD (Resarch and development) yang bertujuan untuk mengetahui bagaimana proses pembuatan aplikasi belajar, kelayakan aplikasi belajar, respon siswa dan guru terhadap aplikasi belajarÂ  berbasis HOTS dimensi metakognitif dengan pendekatan TPACK. Aplikasi belajar berbasis HOTS dimensi metakognitif dengan pendekatan TPACK adalah media pembelajaran interaktif berupa aplikasi android yang berisi menu-menu belajar seperti video pebelajaran, LKPD, E-Book, kuis online multiplayers, dan RPP untuk memberikan gambaran proses kegiatan pembelajaran menggunakan aplikasi belajar. Aplikasi belajar mendapaktan respon positif dari siswa dan guru dengan nilai persentase 91,04% dari 25 responden siswa yang berarti termasuk kategori â€sangat baikâ€, dan 90,80% dari 7 responden guru yang berarti termasuk kategori â€sangat baikâ€ yang menunjukan keberhasilan penelitian ini.Kata Kunci: Aplikasi belajar berbasis HOTS, pendekatan TPACK, dimensi metakognitif, sekolah dasar.